Exogenous glucocorticoids amplify the costs of infection by reducing resistance and tolerance, but effects are mitigated by co-infection. Issue 1900 (10th April 2019) - Schoenle, Laura A.; Moore, Ignacio T.; Dudek, Alana M.; Garcia, Ellen B.; Mays, Morgan; Haussmann, Mark F.; Cimini, Daniela; Bonier, Frances
Abstract : Individual variation in parasite defences, such as resistance and tolerance, can underlie heterogeneity in fitness and could influence disease transmission dynamics. Glucocorticoid hormone concentrations often change in response to fluctuating environmental conditions and mediate changes in immune function, resource allocation and tissue repair. Thus, changes in glucocorticoid hormone concentrations might mediate individual variation in investment in resistance versus tolerance. In this study, we experimentally increased glucocorticoid concentrations in red-winged blackbirds ( Agelaius phoeniceus ) that were naturally infected with haemosporidian parasites, and assessed changes in resistance and tolerance of infection. Glucocorticoid treatment increased burdens of Plasmodium, the parasite causing avian malaria, but only in the absence of co-infection with another Haemosporidian, Haemoproteus . Thus, glucocorticoids might reduce resistance to infection, but co-infection can mitigate the negative consequences of increased hormone concentrations. Glucocorticoid treatment also decreased tolerance of infection. We found no evidence that the inflammatory immune response or rate of red blood cell production underlie the effects of glucocorticoids on resistance and tolerance. Our findings suggest that exogenous glucocorticoids can increase the costs of haemosporidian infections by both increasing parasite numbers and reducing an individual's ability to cope with infection. These effects could scale up to impact populations of both host and parasite.